Kepemimpinan dan Manajemen Konflik berbasis Pendidikan Islam (Studi Kasus di Pondok Pesantren Darul Ihsan Teluk Lerong Ilir, Samarinda) - Achmad Farihin (Fakultas Tarbiyah dan Ilmu Keguruan (FTIK) IAIN Lhokseumawe, 2024)
This study aims to analyze the role of leadership in conflict management at Pesantren Darul Ihsan Teluk Lerong Ilir, Samarinda and its impact on the educational environment. The research employs a qualitative method with a case study approach, where data was collected through interviews, observations, and documentation. The findings reveal that the pesantren leader holds a key role in resolving conflicts through the principles of consultation (syura) and open dialogue based on Islamic values. The application of consultation is evident in resolving various types of conflicts, including interpersonal conflicts among students, group conflicts, and structural conflicts between administrators and educators. By utilizing an approach grounded in Islamic ethics, these conflicts are resolved effectively, creating a more harmonious learning environment, strengthening unity, enhancing discipline, and fostering a work ethic among students and educators. Additionally, the study found that well-managed conflicts can serve as a means for character development, reinforcing integrity and social responsibility in students. In conclusion, Islamic values-based and responsive pesantren leadership plays a significant role in establishing a conducive and sustainable learning atmosphere. This article is expected to contribute to the development of Islamic leadership theory in conflict management within Islamic educational environments.